The Influence Of Advertisement Appeal, Product Quality, And Brand Equity On Head & Shoulders Shampoo Purchase Decision In Surabaya - Herninda Dara Puspita Ayu; Nurhadi Nurhadi (UNIVED Press, 2024)
Purchasing decisions play an important role for companies as they impact profitability and business sustainability. This research aims to identify the influence of advertising appeal, product quality, and brand equity on the purchase decisions of Head & Shoulders shampoo products in Surabaya. The population of this study consists of Head & Shoulders shampoo users who have also watched the